Disentangling the influence of knowledge on attribute non-attendance. (September 2017) - Sandorf, Erlend Dancke; Campbell, Danny; Hanley, Nick
Abstract: We seek to disentangle the effect of knowledge about an environmental good on respondents' propensity to ignore one or more attributes on the choice cards in a discrete choice experiment eliciting people's preferences for increased protection of cold-water corals in Norway. We hypothesize that a respondent's level of knowledge influences the degree to which she ignores attributes. Respondents participated in a quiz on cold-water coral prior to the valuation task and we use the result of the quiz as an ex-ante measure of their knowledge. Our results suggests that a high level of knowledge, measured by a high quiz score, is associated with higher probabilities of attendance to the three non-cost attributes, although this effect is only significant for one of them. A higher quiz score is also associated with a significantly lower probability of attending to the cost attribute. Furthermore, although being told your score has mixed directional effects on attribute non-attendance, it does not significantly affect the probability of attending to any of the attributes. Finally, allowing for attribute non-attendance leads to substantially lower conditional willingness-to-pay estimates. This highlights the importance of measuring how much people know about the goods over which they are choosing, and underlines that more research is needed to understand how information influences the degree to which respondents ignore attributes. Highlights: We disentangle the effect of knowledge on attribute processing strategies. We use a respondent's score on a quiz as an ex ante measure of knowledge. High knowledge is associated with a higher predicted probability of attendance. Receiving an external signal about the extent of your knowledge does not affect attribute non-attendance. Accounting for attribute non-attendance leads to lower willingness-to-pay estimates.